Endoparasite worms infestation on Skipjack tuna Katsuwonus pelamis from Sibolga waters, Indonesia - Eri Yusni; Raihan Uliya (Syiah Kuala University, 2019)
Skipjack tuna Katsuwonus pelamis is one of the commercial species of fishes in Indonesia frequently caught by fishermen in Sibolga waters, North Sumatra Province. There is, however, presently no study conducted on the endoparasites infestation in these fishes. Therefore, the objectives of the present study were to identify endoparasitic worms and examine the intensity level in skipjack tuna K. pelamis from Sibolga waters. Sampling was conducted in Debora Private Fishing Port, Sibolga from 4th to 18th June 2019 and a total of 20 fish samples with weight ranged between 740 g and 1.200 g and length from 37.2 cm to 41.4 cm were analyzed in the study. The identification of the worm was conducted in the laboratory using a stereo microscope. The results showed seven species or genera of worms were found in the intestine and stomach of the fish with varying level of intensity and incidence. For example, Echinorhynchus sp. was found with 100% intestinal and 10% stomach incidences at a total intensity of 8.5; Acanthocephalus sp. with 25% intestinal incidence and 1.6 intensity, Rhadinorhynchus sp. with 25% intestinal and 5% stomach incidences, and 1.5 intensity; Leptorhynchoides sp. with 25% intestinal incidences, and 1 intensity; Neoechinorhynchus sp. with 25% intestinal incidences, and 1.4 intensity; Pomphorhynchus sp. with 10% intestinal incidence, and 1.5 intensity; andApororhynchus sp. with 10% intestinal incidences and 1 intensity. Echinorhynchus sp. was concluded to have the highest incidence and intensity.